Parents' experiences of their child's return to school following acquired brain injury (ABI): A systematic review of qualitative studies. (6th June 2016) - Andersson, Kerstin; Bellon, Michelle; Walker, Ruth
Abstract: Objective : To examine parents' experiences during their child's return to school following ABI. Research design : Systematic literature review. Methods : Six electronic databases relevant to the fields of brain injury and education were searched between 1980–2015. In addition, two qualitative journals and references from articles were hand-searched for further literature. Search results were screened independently by two reviewers for relevance. Studies meeting the inclusion criteria were analysed using the McMasters Critical Review Form for Qualitative Studies. Results : Two hundred and sixteen articles were screened after duplicates had been removed and 11 were assessed for relevance, resulting in six full text articles for review. The quality of studies was mixed, with only two presenting a high number of quality indicators for qualitative research. Ten themes were identified and grouped into three clusters: influencing factors (environment, school, parent and child factors); features of interaction (information, communication and collaboration); and quality levels of outcome (conflict, coping and construction of new roles and identities). Conclusions : Parents' experiences are influenced by the quality of information, communication and collaboration between the school, health professionals and the family. Further well designed qualitative studies examining parents' experiences and support needs are required.